Experimental Modal Analysis of Civil Engineering Structures - Álvaro Cunha (2006)
The evolution of experimental modal analysis in the civil engineering structures, from input-output to output-only modal identification techniques, is discussed. The conventional modal testing is based on estimating a set of frequency responses functions (FRFs) relating the applied force and corresponding response at several pairs of points along the structure with enough high spatial and frequency resolution. The main drawbacks are the relatively low frequency resolution of the spatial estimates and the lack of energy to excite some relevant modes of vibration. There is currently a tendency worldwide to explore and improve the potential of output-only modal identification techniques, whose efficiency and accuracy have been illustrated with various applications. The techniques that may be used under normal operation conditions can provide a solid basis for developing finite-element correlation analyses, finite-element updating and validation, and implementing vibration-control devices.